A class of morphing shell structures satisfying clamped boundary conditions. (15th March 2016) - Brunetti, M.; Vincenti, A.; Vidoli, S.
Abstract: Many examples of multi-stable shell structures have been recently proposed with the underlying hypothesis of the shell being completely free on its boundary. We describe a class of shallow shells which are bistable after one of their sides is completely clamped. This result, which has relevant technological implications, is achieved by a suitable design of the initial, stress-free, shape.